Effect of GnRH Analog Therapy on Adult Height in Girls with Idiopathic Central Precocious Puberty - Reiko Saito; Yukihiro Hasegawa (Endocrines, 2025)
Precocious puberty (PP) is characterized by the early onset of secondary sexual characteristics and accelerated growth, which often result in compromised adult height (AH). Central precocious puberty (CPP), a subset of PP, is treated with gonadotropin-releasing hormone analogs (GnRHa) to suppress premature hormonal activation and delay epiphyseal closure, thereby preserving height potential. The present review examined the effects of GnRHa on AH outcomes in girls with idiopathic CPP. Although AH is greater with GnRHa therapy than without it, the treatment does not consistently restore the patient’s genetic potential. The benefits of the treatment are most evident in girls in whom idiopathic CPP is diagnosed before 6 years of age and they achieve a height gain of 4.5–14.1 cm, which is unattainable without treatment. However, the treatment of older children (ages 6–8) shows conflicting results, with the AH outcome varying among previous reports. In particular, slowly progressive CPP is known to have a favorable height prognosis even without treatment. Another factor influencing the AH prognosis is the timing of GnRHa discontinuation; the best time to discontinue GnRHa therapy for the best AH outcome is reportedly the bone age of approximately 12 years. In conclusion, although GnRHa therapy significantly improves the AH, especially in early-onset CPP, its effectiveness is uncertain in borderline or late-onset cases. Further research is required to formulate more precise criteria for patient selection and treatment discontinuation to optimize height outcome in girls with idiopathic CPP.